The Role of Fraud Pentagon Elements in Financial Statement Fraud: Evidence from Islamic Commercial Banks in Indonesia - Kharimah, Khaerohtun Nurul; Nugraha, Nyata; Budiyono, Iwan; Arumsari, Vita (Economica: Jurnal Ekonomi Islam, 2024)
Islamic banks in Indonesia have experienced rapid growth relative to their conventional counterparts. However, this expansion is accompanied by challenges, notably the prevalence of fraudulent practices. This study aims to analyze the influence of the fraud pentagon on Financial Statement Fraud (FFR) in Islamic Commercial Banks in Indonesia from 2018 to 2023, both collectively and individually. The study population comprises all Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK) as of December 2023. Using a purposive sampling method, ten Islamic commercial banks were selected for analysis. The research employs a Multiple Linear Regression Analysis model, executed in EViews 13. The findings reveal that, collectively, the elements of Pressure (ROA), Opportunity (BDOUT), Rationalization (TACC), Capability (DCHANGE), and Arrogance (CEO PICTURE) significantly impact FFR. Individually, Pressure (ROA), Opportunity (BDOUT), and Rationalization (TACC) have a positive and significant effect on FFR, while Capability (DCHANGE) and Arrogance (CEO PICTURE) exhibit a positive but non-significant effect.